2019
DOI: 10.3947/ic.2019.51.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Severe Fever with Thrombocytopenia Syndrome in the Agricultural Population of Jeju Island, Korea, 2015–2017

Abstract: BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is a tick-borne zoonotic disease that is caused by the SFTS virus (SFTSV), and exhibits an overall mortality rate of approximately 20.0% in Korea. Most cases of this disease have been reported in Korea, East China, and Japan, and it mostly affects outdoor workers and farmers. This study aimed to investigate the seroprevalence of SFTSV among healthy farmers on Jeju Island, Korea.Materials and MethodsIn this prospective cross-sectional study, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…To investigate the levels of neutralizing antibodies to SFTSV, we collected 19 serum samples from 11 patients (non-surviving patients; n =6, mean age: 73.3 and surviving patients; n =5, mean age: 68.8), which were laboratory confirmed at Jeju National University from May 2013 to October 2019, Jeju, South Korea, and 7 serum samples from 5 healthy residents (mean age: 69.8) living in endemic areas who were positive for SFTSV IgG from November 2015 to April 2017 ( Yoo et al., 2019 ) ( Table 1 ). This study was approved by the Institutional Review Board (IRB) of Jeju National University Hospital.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the levels of neutralizing antibodies to SFTSV, we collected 19 serum samples from 11 patients (non-surviving patients; n =6, mean age: 73.3 and surviving patients; n =5, mean age: 68.8), which were laboratory confirmed at Jeju National University from May 2013 to October 2019, Jeju, South Korea, and 7 serum samples from 5 healthy residents (mean age: 69.8) living in endemic areas who were positive for SFTSV IgG from November 2015 to April 2017 ( Yoo et al., 2019 ) ( Table 1 ). This study was approved by the Institutional Review Board (IRB) of Jeju National University Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time RT-PCR showed that all the patients ( n =11) were positive for SFTSV, and 6 healthy residents were negative for SFTSV. Antibody detection was performed, and IgG was detected in the serum of all patients and 6 healthy residents ( Yoo et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cropland areas are associated with high risk for infection (2,3,6). Northeast Jeju Island, which includes SH, AW, and HD, has many farms and wetlands, and the IR of SFTSV in ticks peaked there in July, August, and September.…”
Section: Research Lettersmentioning
confidence: 99%
“…A previous study reported that the minimum infection rate of SFTSV in infected ticks was lower (0.37%) on Jeju Island than in other collection areas (1.97%) (4). However, 7%-14% SFTSV seropositivity was identified in domestic and wild animals (4-5), and 2%-5% SFTSV seropositivity was identified in a healthy population in South Korea (6). Therefore, our aim was to investigate the SFTSV infection rate (IR) in ticks in the region with the highest endemicity, Jeju Island, and to analyze the relationship between the geographic distribution of ticks and SFTSV and human cases of SFTS.…”
mentioning
confidence: 99%